Nanodiamond pretreatment for the modification of diamond electrodes by platinum nanoparticles - Hu, J; Lu, X; Foord, J (2010)
The preparation of Pt-modified diamond electrodes by electrodeposition is known to be hampered by poor particle adhesion and a lack of uniformity in the spatial distribution of the deposit over the electrode surface. Here we demonstrate the results can be improved significantly if the electrode is given a simple ultrasonic treatment in the presence of diamond powders prior to electrodeposition. An improvement in spatial distribution and a higher Pt dispersion are seen and, especially, a greater Pt particle stability is observed. Application of these Pt modified diamond electrodes in the electrochemical oxidation of hydrogen peroxide is demonstrated. © 2010 Elsevier B.V. All rights reserved.